BUSINESS PLAN BISNIS SOFTWARE HOUSE CONTURE DI SURABAYA - Antonius Redo Adi Siswanto (Perpustakaan Universitas Surabaya, 2014)
“Conture” is a house-software business that runs in the field of information technology with a motto of ‘a convinient way to reach a better future’. Conture provides consultation service and the creation of business application to help middle level business activities in running their business. This application provides module service for marketing, logistic, accounting etc. compatible with the needs of the middle level business activities.